INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMBINAAN KARAKTER SISWA PADA SMP NEGERI 10 KOTA SORONG - Samsudin Datu (Pascasarjana IAIN Sorong, 2019)
This research deals with the Internalization of Islamic Education Values in Character Building at SMPN 10 of Sorong City. The purposes of this study are: first, to determine the internalization of Islamic education values at SMPN 10 of Sorong City; second, to examine the forms of teacher efforts in developing the character values of SMPN 10 of Sorong City; and third, to formulate opportunities and challenges of internalization of Islamic education Values in fostering character at SMPN 10 of Sorong City. The results showed that First, the internalization of Islamic education values at SMPN 10 of Sorong City in this study included the preliminary stages, presentation of the core subjects and closing. Indicators of preliminary learning activities include greeting, delivering of perception, delivering of TKP, and drawing of attention. In the use of instructional media, the teachers of SMPN 10 of Sorong City are equipped with complete facilities so that the method is more varied. Second, the form of teacher's efforts in developing the character values of SMPN 10 of Sorong City is through integrated supervision of all school components of student behavior, providing motivation through advice and stories of successful people, implementing learning strategies with active learning models to enhance activities learning which is a follow-up to the results of the agreement of the teachers meeting at SMPN 10 of Sorong City. Students who have high achievements also have good character attitude. Third, Opportunities and challenges of the internalization of Islamic education values in character building at SMPN 10 of Sorong City are the existence of a strong desire and determination of stakeholders to advance the school and the strong commitment of teachers at SMPN 10 of Sorong City to develop Education, and Community